New method to separation and purification of two bioactive compounds from powder of turmeric plant by RP-HPLC technique (Eurasian Journal of Research, Development and Innovation, 2024)
Two compounds were separated successfully. The used method was suitable for getting a high purified compound for each one . There is the ability to get more than one high purified compound from alcoholic extract for curcumin